Fluid Deficiency and Its Effect on Some Biological Variables for Athletes - MostafaAbdo, Mona; SherinHussien, (International Journal of Psychosocial Rehabilitation, 2024)
This paper to study Lack of fluids on the water condition of the body and Lack of fluid on aerobic and anaerobic work, This research is within the knowledge of researchers among the few studies conducted on the effect of fluid deficiency on sports performance, and it answers some questions related to sports training during the period of fluid deficiency and the effect of fluid deficiency on competitions that may take place during the period of fluid deficiency, and it opens horizons Research to answer many of the questions that many trainers ask about the best timing for training and whether or not the pressures on the body due to lack of fluids can be used to induce an adaptation that may have a positive effect on the high level of performance, as is the case when training at altitudes or not. METHODS: The research sample was deliberately chosen from among athletes, and their number reached 10 players who volunteered to participate in this study and conducted its experiment, The two researchers used the descriptive approach (case study) due to its relevance to the nature of the objectives and procedures of this study. RESULTS: There are no statistically significant differences in the amount of water in the body between the normal state and the state of lack of fluids, and then there may be an adaptation of the body to the lack of water by increasing the secretion of the antidiuretic hormone, which works to retain the largest amount of water in the body, as well as increasing the secretion of the hormone Aldosterone, which works to get rid of potassium salts over the needs of the body and to retain sodium and water, which increases the volume of fluids in the body, and both work to maintain the osmolality of body fluids at normal limits, and these results are consistent with the results of studies. Conclusions: The effect of fluid deficiency on the body's water condition does not reach the degree of dehydration (> 2% of body weight), which can affect the physiological condition and thus athletic performance. aerobic and anaerobic activity is not affected by the fluid deficiency.